Methodological Readiness of Musical Art Master’s Degree Students: A Theoretical Research - Ovcharenko, Nataliya; Matveieva, Olha; Chebotarenko, Olha; Koehn, Natalya (Journal of History Culture and Art Research, 2019)
Modern trends of social development, processes of science modernization along with information and technologies integrations in education, make the search of ways to improve the scientific training of musical art masters timely relevant, which involves a thorough mastery of the scientific basics of musical art and more to the point – methods of their knowledge in the institution of higher music-pedagogical education. The scientific training of master’s degree students of musical art includes methodological training, which is based not only on knowledge of the theory and methodology of musical art but also on scientific methods of their study. Master’s degree students should know the scientific innovations of music performance and music pedagogics, to analyze, synthesize, generalize, systematize, structure, classify, conduct experimental research, interpret, evaluate, use them in their work with students, etc. The methodological readiness of master’s degree students of musical art should be regarded from the standpoint of personally-oriented, activity and competence approaches, i.e., it is a professional-personal entity based on the motivation to such a kind of activity, a complex of methodological knowledge, skills, and psychological capacities to be applied into practice. In order to carry out the process effectively, we have defined the structure of methodological readiness of master’s degree students of musical art which includes: motivation-and-need, informational-cognitive, science-and-activity, reflexive-evaluative and self-improving components; certain criteria, factors and levels of methodological readiness formation of musical art masters have been considered. For the sake of master’s degree students’ methodological training improvement, there were developed and theoretically substantiated the content, forms and methods of such training in the process of instrumental and vocal training during the Master’s degree course.